Regenerative Potential of Platelet-Rich Fibrin Releasate Combined with Adipose Tissue–Derived Stem Cells in a Rat Sciatic Nerve Injury Model. (11th June 2020) - Chuang, Ming-Hsi; Ho, Li-Hsing; Kuo, Tzong-Fu; Sheu, Shi-Yuan; Liu, Yu-Hao; Lin, Po-Cheng; Tsai, Yu-Chen; Yang, Chang-Huan; Chu, Chi-Ming; Lin, Shinn-Zong
Sciatic nerve injuries, not uncommon in trauma with a limited degree of functional recovery, are considered a persistent clinical, social, and economic problem worldwide. Accumulating evidence suggests that stem cells can promote the tissue regeneration through various mechanisms. The aim of the present study was to investigate the role of adipose tissue–derived stem cells (ADSCs) and combine with platelet-rich fibrin releasate (PRFr) in the regeneration of sciatic nerve injury in rats. Twenty-four Sprague-Dawley rats were randomly assigned to four groups, a blade was used to transect the left hindlimb sciatic nerve, and silicon tubes containing one of the following (by injection) were used to bridge the nerve proximal and distal ends (10-mm gap): group 1: untreated controls; group 2: PRFr alone; group 3: ADSCs alone; group 4: PRFr + ADSCs-treated. Walking function was assessed in horizontal rung ladder apparatus to compare the demands of the tasks and test sensitivity at 1-mo interval for a total of 3 mo. The gross inspection and histological examination was performed at 3 mo post transplantation. Overall, PRFr + ADSCs-treated performed better compared with PRFr or ADSCs injections alone. Significant group differences of neurological function were observed in ladder rung walking tests in all treated groups compared to that of untreated controls ( P < 0.05). This injection approach may provide a successfully employed technique to target sciatic nerve defects in vivo, and the combined strategy of ADSCs with PRFr appears to have a superior effect on nerve repair.